2007
DOI: 10.1197/jamia.m2384
|View full text |Cite
|
Sign up to set email alerts
|

Unintended Consequences of Information Technologies in Health Care--An Interactive Sociotechnical Analysis

Abstract: Many unintended and undesired consequences of Healthcare Information Technologies (HIT) flow from interactions between the HIT and the healthcare organization's sociotechnical system-its workflows, culture, social interactions, and technologies. This paper develops and illustrates a conceptual model of these processes that we call Interactive Sociotechnical Analysis (ISTA). ISTA captures common types of interaction with special emphasis on recursive processes, i.e., feedback loops that alter the newly introduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
421
0
9

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 539 publications
(436 citation statements)
references
References 51 publications
6
421
0
9
Order By: Relevance
“…We framed our study with sociotechnical systems theory, which has been used and discussed prominently in the medical informatics literature [4][5][6][7][8][9][10][11][12][13][14]. Although there is no one "sociotechnical approach" [4], studies that rely on a sociotechnical perspective all have a high-level recognition that organizational and health systems at large have a substantial influence in shaping HIT and that the technology and context are intertwined [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We framed our study with sociotechnical systems theory, which has been used and discussed prominently in the medical informatics literature [4][5][6][7][8][9][10][11][12][13][14]. Although there is no one "sociotechnical approach" [4], studies that rely on a sociotechnical perspective all have a high-level recognition that organizational and health systems at large have a substantial influence in shaping HIT and that the technology and context are intertwined [5].…”
Section: Introductionmentioning
confidence: 99%
“…One example is the "forgotten" power of paper as EHRs began to take shape; that is, how the paper record evolved within the sociotechnical work practices and how many of these nuances were lost with the introduction of the EHR [9]. A clear recognition of the social and technical subcomponents, including the recursive relationships within the day to day practice of an organization, is particularly well-articulated in some recent studies of HIT [10][11][12], where there is often a risk of technology-driven design and implementation without sufficient regard to the social subsystem [12]. Westbrook and others summarize that HIT problems are complex sociotechnical problems and that each subsystems within the sociotechnical system must be considered in relation to each other since optimization of one may negatively impact the other [14].…”
Section: Introductionmentioning
confidence: 99%
“…Implementation and use of health information technology typically involves significant changes to clinical processes and workflows, which can have unintended positive and negative effects on care quality. [17][18][19]30 While most prior research has been conducted in inpatient settings, it has shown that physicians often find that EMR interfaces create additional work by forcing them to click through many screens and options as well as imposing tasks previously handled by others, especially when placing orders. 31,32 Similar effects in primary care may take away significant visit time and reduce physician's cognitive performance in terms of ability to provide comprehensive care.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Discouragingly, related work describes unintended consequences of EMRs that result from increasingly shifting the physician-patient interaction to a physician-computer interaction. [17][18][19] Thus, there is a continued need for studies that describe the general effect of EMR implementations on health care quality. This is especially important for complex patients.…”
Section: Introductionmentioning
confidence: 99%
“…3 Early in the science of studying EHR-UCs, an interactive sociotechnical framework was proposed to specify relationships of EHR-UCs to organizational, social, and workflow factors. 4 As depicted in that framework, as the EHR is implemented, the social system is proposed to adapt while numerous factors influence how the technology is used.…”
Section: Introductionmentioning
confidence: 99%